Isolation and identification of Rhizobium from non-saline coastal soils of Bangladesh and preparation of mother culture (Asian Journal of Medical and Biological Research, 2020)
Nitrogen is the essential mineral macro nutrients which are required for the maximum magnification and yield of agriculturally paramount crops. Microbial inoculants may supplement and abbreviate the dependency on synthetic costly N-fertilizers in reverence of crop yield. The categorical objectives of the research works are to isolate and identify the Rhizobium from culled soils. The ability of soil microorganisms to fix atmospheric nitrogen is an important trait in promoting plant growth and increasing crop yield. The study was conducted for the isolation and identification of nitrogen fixing bacteria from saline and non-saline soils of different locations of tidal floodplain region of Bangladesh. Six Rhizobium strains were isolated and purified. The isolates were preliminary identified on the basis of their morphological and biochemical characteristics. Based on the results, it can be concluded that the isolates possess great potential to be developed as biofertilizers to enhance soil fertility and plant growth. However, their performance under green house and field conditions should be assessed afore being recommended for biofertilizer production and their applications.Asian J. Med. Biol. Res. June 2020, 6(2): 222-228